The Effect of Different Concentration Salt on Quality and Formaldehyde Content in Pindang Semar Fish (Mene maculate) - Asriani, Asriani; Sayuti, Mohammad; Sahira, Reza Waldani (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2022)
Semar fish is one of the most consumed fish in Indonesia. In 2016, 14 tons of fresh semar fish containing formalin were destroyed by the DKI Jakarta DKPKP. The purpose of this study was to identify the quality of raw materials, product quality and formaldehyde content of Pindang Semar fish (Mene maculata) with different salt content treatments. Organoleptic testing refers to SNI 2729:2013, TVB-N refers to SNI 2354.8-2009 (raw material), ash refers to SNI 2354.1:2010, water refers to SNI 2354.2:2015, protein refers to SNI 01-2354.4-2006, fat refers to SNI 01-2354.3 -2006) and formaldehyde refers to SNI 2354-18-2018. The results showed organoleptic semar fish was still fresh with a TVB-N content of 14.18 mg-N/100. The highest sensory test value of Semar Pindang fish was at a concentration of 5% with a value of 8. The results of the salt level test showed a significant difference from the different salt concentrations given. The results of the proximate test on the fat content, water content, ash content test showed significant differences in the treatment of different salt concentrations. The test results for formaldehyde levels with different salt concentrations showed a decrease but were not significantly different. The provision of different salt concentrations had an effect on the quality and decrease of formaldehyde in Semar Pindang fish.